FENOMENA MALIM DALAM TRADISI SENI KUDA LUMPING - Luffita Rizky (Institut Seni Budaya Indonesia (ISBI) Bandung, 2018)
ABSTRACT Kuda Lumping art performance is seen as a reality of cultural arts that is dense with mystical cultural traditions. The show takes the form of helaran which features Kuda Lumping dance accompanied by tetabuhan music that reinforces the sacred nuances as its trademark. The presence of a Malim in the performance of Kuda Lumping, is seen as a central role that controls the performance of the show. Malim acts as a person who is able to communicate transcendently using his spells. This was an attempt to invite the spirits to enter together with the spirit of the player Kuda Lumping to become possessed (trance).This paper is a form of scientific description of the results of a field study using descriptive analysis methods as one of the characteristics of qualitative research. The approach uses phenomenological studies as an effort to elevate the cultural reality surrounding the tradition of performing Kuda Lumping art. The object studied was taking samples of Malim figures who were considered representative with the depth of their knowledge and experience while becoming Malim Kuda Lumping. Research in the form of a description of this analysis will eventually become a scientific article that can be published in scientific journals. Keywords: Malim, Kuda Lumping, Kasurupan and Transcendent. ABSTRAK Pertunjukan seni Kuda Lumping dipandang sebagai sebuah realitas seni budaya yang kental dengan tradisi budaya mistisnya. Pertunjukannya berbentuk helaran yang menampilkan tarian Kuda Lumping dengan diiringi musik tetabuhan yang mempertegas nuansa sakral sebagai ciri khasnya. Kehadiran seorang Malim dalam pertunjukan Kuda Lumping, dipandang sebagai peran sentral yang mengendalikan jalannya pertunjukan. Malim berperan sebagai sosok yang mampu berkomunuikasi secara transenden dengan menggunakan mantra-mantranya. Hal tersebut sebagai upaya mengundang roh halus untuk masuk menyatu dengan roh si pemain Kuda Lumping hingga menjadi kerasukan (trans).Tulisan ini merupakan bentuk deskripsi ilmiah hasil dari sebuah penelitian lapangan dengan menggunakan metode deksripsi analisis sebagai salah satu ciri bentuk penenlitian kualitatif. Adapun pendekatannya menggunakan studi fenomenologi sebagai sebuah upaya mengangkat realitas budaya yang terdapat di seputar tradisi pertunjukan seni Kuda Lumping. Objek yang dikaji adalah mengambil sampel tokoh Malim yang dianggap representatif dengan kedalaman ilmu dan pengalamannya selama menjadi Malim Kuda Lumping. Penelitian dalam bentuk deskripsi analisis ini, pada akhirnya akan dijadikan artikel ilmiah yang dapat dimuat di jurnal ilmiah. Kata Kunci: Malim, Kuda Lumping, Kasurupan dan Transenden.